Opposite and redundant roles of the two Drosophila perilipins in lipid mobilization. - Bi, J.; Xiang, Y.; Chen, H.; Liu, Z.; Grönke, S.; Kühnlein, R.P.; Huang, X. (Journal of Cell Science, 2012)
Lipid droplets are the main lipid storage sites in cells. Lipid droplet homeostasis is regulated by the surface accessibility of lipases. Mammalian adipose triglyceride lipase (ATGL) and hormone-sensitive lipase (HSL) are two key lipases for basal and stimulated lipolysis, respectively. Perilipins, the best known lipid droplet surface proteins, can either recruit lipases or prevent the access of lipases to lipid droplets. Mammals have five perilipin proteins, which often exhibit redundant functions, precluding the analysis of the exact role of individual perilipins in vivo. Drosophila have only two perilipins, PLIN1/LSD-1 and PLIN2/LSD-2. Previous studies revealed that PLIN2 is important for protecting lipid droplets from lipolysis mediated by Brummer (BMM), the Drosophila homolog of ATGL. In this study, we report the functional analysis of PLIN1 and Drosophila HSL. Loss-of-function and overexpression studies reveal that unlike PLIN2, PLIN1 probably facilitates lipid mobilization. HSL is recruited from the cytosol to the surface of lipid droplets under starved conditions and PLIN1 is necessary for the starved induced lipid droplet localization of HSL. Moreover, phenotypic analysis of plin1;plin2 double mutants revealed that PLIN1 and PLIN2 might have redundant functions in protecting lipid droplets from lipolysis. Therefore, the two Drosophila perilipins have both opposite and redundant roles. Domain swapping and deletion analyses indicate that the C-terminal region of PLIN1 confers functional specificity to PLIN1. Our study highlights the complex roles of Drosophila perilipin proteins and the evolutionarily conserved regulation of HSL translocation by perilipins.